Multifactor Portfolio Efficiency and Multifactor Asset Pricing - Fama, Eugene F. (Journal of Financial and Quantitative Analysis, 1996)
The concept of multifactor portfolio efficiency plays a role in Merton's intertemporal CAPM (the ICAPM), like that of mean-variance efficiency in the Sharpe-Lintner CAPM. In the CAPM, the relation between the expected return on a security and its risk is just the condition on security weights that holds in any mean-variance-efficient portfolio, applied to the market portfolio M. The risk-return relation of the ICAPM is likewise just the application to M of the condition on security weights that produces ICAPM multifactor-efficient portfolios. The main testable implication of the CAPM is that equilibrium security prices require that M is mean-variance-efficient. The main testable implication of the ICAPM is that securities must be priced so that M is multifactor-efficient. As in the CAPM, building the ICAPM on multifactor efficiency exposes its simplicity and allows easy economic insights.